The Effect of Biogas Purification Process Using Calcium Oxide-Based Sorbents on the Diffusion Flame Combustion Characteristics - Dani Hari Tunggal Prasetiyo; Djoko Wahyudi; Alief Muhammad (Journal of Earth Energy Science, Engineering, and Technology, 2021)
Biogas is an alternative energy source that could solve two problems at once, the problem of environmentally friendly energy needs and the problem of waste treatment. One of the sources of biogas is obtained from anaerobic bacterial fermentation of cow dung waste. The biogas fermentation process produces impurities such as carbon dioxide (CO2) as a combustion inhibitor. Carbon dioxide will inhibit the combustion reaction, resulting in incomplete combustion. The biogas purification process is needed to reduce the amount of carbon dioxide in the biogas. The purification process is carried out using an absorbent compound of calcium oxide (CaO) to bind carbon dioxide contained in the biogas. Thus, the purpose of this study was to analyze the effect of the biogas purification process using calcium oxide on the characteristics of the diffusion flame produced by combustion. The research was conducted experimentally using the physicochemical-absorption method of purification by flowing biogas through a purificator device that contained a purification solution. After passing through the purification solution, the biogas was regulated at a fuel flow rate of 3 liters/min and then proceed to the bunsen burner. The results showed that purification affected increasing the characteristics of the diffusion flame combustion due to the reduced amount of carbon dioxide in the biogas. This is indicated by increasing the purification molarity, it also increases the flame speed of combustion and the flame angle, as well as a decrease in the flame height.